Comparison of 3% Hypertonic Saline and Mannitol in the Management of Children with Raised Intracranial Tension: A Research Protocol - Lavanya Ramakrishnan; Revatdham Meshram (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Raised Intracranial Tension (ICT) is a common medical emergency with varied aetiology. Immediate medical or surgical intervention is mandated in most cases. Conservatively, osmotherapy with 3% Hypertonic Saline (HTS) or Mannitol is the mainstay to reduce raised ICT. Additionally, the patient may also need surgical intervention along with osmotherapy. The need for the study: Cerebral oedema and raised ICT in children and its treatment protocol are under-estimated and need further research and study in terms of identification of the condition and the choice of osmotherapy, which is the cornerstone in treating raised ICT among others. Aim: To analyse the role of 3% HTS and mannitol and their individual efficacy in reducing intracranial pressure in children. Materials and Methods: An open-labeled, prospective study, where alternately patients between the age group of one month to 16 years admitted to the Pediatric Intensive Care Unit (PICU) of a designated tertiary care hospital situated in the state of Maharashtra, in India from November 2020 to October 2022, diagnosed to have or showing signs and symptoms of raised ICT will be given 3% HTS or Mannitol after considering the exclusion criteria for each if any will be conducted. The patient will be treated with a fixed dose of either drug as pre-decided by the principal investigator and the secondary investigator and the patient will be monitored within the next hour for immediate effects and improvement in the clinical state of the patient as well as the immediate general outcome in terms of vitals and sensorium and final outcome in terms of discharge rate with neuromorbidity, if any, or resulting death in patients treated with either drug will be noted. The chi-square test, Fischer’s-exact test for categorical data, and independent t-test for continuous data with normal distribution will be used to assess the relationship between various demographic, clinical, and aetiological characteristics and outcomes. The parameters that will be compared are sensorium, heart rate, respiratory rate and pattern, and Blood Pressure (BP) at admission. The above parameters will be monitored immediately after infusion of osmotherapy and the final outcome, as mentioned above, of patients on either of the drugs will be noted. The p-value of less than 0.05 will be considered significant.